Pengertian dan Manfaat Produk Halal bagi Konsumen - Muhammad Hisyam Fathoni; Romi Faslah (Jurnal Ekonomi dan Bisnis Digital, 2025)
Halal products have become a global phenomenon that attracts not only Muslim consumers but also non-Muslim consumers worldwide. This study comprehensively discusses the definition of halal products and analyzes various benefits obtained by consumers from choosing halal-certified products. The research aims to explore the fundamental reasons why consumers are increasingly interested in halal products, ranging from food safety aspects, product quality, to ethical and spiritual values. Using a descriptive analytical approach through literature review methodology, this study examines the comprehensive understanding of halal products including raw material criteria, production processes, and certification systems. The findings reveal that consumers choose halal products due to religious motivations, quality assurance, healthy lifestyle trends, and social-environmental concerns. The benefits obtained include health and food safety assurance, spiritual and psychological satisfaction, social and ethical values, and economic advantages. The halal industry faces challenges in international standard harmonization and supply chain complexity, yet offers significant opportunities for development through digitalization and market expansion.